2016
DOI: 10.1063/1.4959106
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-related complexes in Li-diffused ZnO single crystals

Abstract: Zinc oxide (ZnO) is a wide band gap semiconductor and a potential candidate for next generation white solid state lighting applications. In this work, hydrogen-related complexes in lithium diffused ZnO single crystals were studied. In addition to the well-known Li-OH complex, several other hydrogen defects were observed. When a mixture of Li2O and ZnO is used as the dopant source, zinc vacancies are suppressed and the bulk Li concentration is very high (>1019 cm−3). In that case, the predominant hydroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…It has been interesting to note that pristine, "undoped" ZnO as often reported in the literature in fact has a finite amount of H in it-either by accident (synthesis through wet-chemical routes or ALD, MOCVD etc) or intentional. 1 The other major defect in ZnO are oxygen vacancies and to a smaller possibility, Zn interstitials. All three of these defect types, viz., hydrogen (interstitial H = H i + é and substitutional), oxygen vacancies (V O + 2é) and Zn interstitials (Zn i + 2é) generally act as background donors, leading to n-type character in "undoped" ZnO.…”
mentioning
confidence: 99%
“…It has been interesting to note that pristine, "undoped" ZnO as often reported in the literature in fact has a finite amount of H in it-either by accident (synthesis through wet-chemical routes or ALD, MOCVD etc) or intentional. 1 The other major defect in ZnO are oxygen vacancies and to a smaller possibility, Zn interstitials. All three of these defect types, viz., hydrogen (interstitial H = H i + é and substitutional), oxygen vacancies (V O + 2é) and Zn interstitials (Zn i + 2é) generally act as background donors, leading to n-type character in "undoped" ZnO.…”
mentioning
confidence: 99%
“…It was observed that Li generates additional holes at the Zn substitution site, while it generates additional electrons at the interstitial site. It can be hypothesized that Li serves as a defect mediator in ZnO NPs [32,33].…”
Section: Field Emission Scanning Electron Microscopy (Fesem)mentioning
confidence: 99%
“…Zinc oxide is an n‐type semiconductor with a wide bandgap of 3.3 eV and high exciton binding energies of around 60 meV at room temperature 1,2 . The native electronic conduction in ZnO is ascribed to point defects such as oxygen vacancies, zinc interstitials, and finite amounts of hydrogen—either by accident or intentional 3,4 . The oxygen vacancies in ZnO ( V O •• ) have relatively low formation energies (≈3.72 eV) 5 ; therefore, they are prevalent point defects, but sluggish ion conductors owing to their relatively large migration energy (2.4 eV) 5 .…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The native electronic conduction in ZnO is ascribed to point defects such as oxygen vacancies, zinc interstitials, and finite amounts of hydrogen-either by accident or intentional. 3,4 The oxygen vacancies in ZnO (V O •• ) have relatively low formation energies (≈3.72 eV) 5 ; therefore, they are prevalent point defects, but sluggish ion conductors owing to their relatively large migration energy (2.4 eV). 5 On the other hand, zinc interstitials (Zn i •• ) have high formation energies (≈6.35 eV) but are easily annihilated from ZnO even at room temperature because of low migration energies (0.57 eV).…”
Section: Introductionmentioning
confidence: 99%